Breve recorrido histórico sobre el Monasterio de Canonesas Regulares del Santo Sepulcro de Zaragoza. Historia de una identidad, una historia desde dentro: A brief historical overview of the Monastery of Regular Canonesses of the Holy Sepulchre in Zaragoza. History of an identity, a history from within. - Gómez Arbiol, Vicente (Artigrama, 2025)
Resumen El Monasterio de Canonesas Regulares del Santo Sepulcro de Zaragoza tiene una historia de vida ininterrumpida de más de 700 años, marcada por transformaciones y desafíos. Fundado inicialmente en 1300 por Marquesa Gil de Rada en Híjar, la comunidad se trasladó a Zaragoza en 1306. Las canonesas y figuras clave como Fray Martín de Alpartir promovieron la construcción del monasterio en el siglo XIV. En el siglo XVI, la imposición de la clausura, derivada del Concilio de Trento, generó conflictos con las religiosas, quienes se resistieron a las restricciones. El siglo XVII fue un siglo de apogeo y cultura dentro de la clausura conventual. A lo largo del siglo XIX, el monasterio sufrió los efectos de la guerra y la inestabilidad política, en el siglo XX experimentó una renovación tras el Concilio Vaticano II. El monasterio sigue siendo un lugar de espiritualidad y conserva un rico patrimonio, testigo de la historia y la evolución de la comunidad. Abstract The Monastery of Regular Canonesses of the Holy Sepulchre of Saragossa has an uninterrupted life history of more than 700 years, marked by transformations and challenges. Initially founded in 1300 by Marquesa Gil de Rada in Híjar, the community moved to Saragossa in 1306. The canonesses and key figures such as Fray Martín de Alpartir, promoted the construction of the monastery in the 14th century. In the 16th century, the imposition of enclosure, derived from the Council of Trent, generated conflicts with the nuns, who resisted the restrictions. The seventeenth century was a century of heyday and culture within the conventual enclosure. Throughout the 19th century, the monastery suffered the effects of war and political instability; in the 20th century it underwent a renewal after the Second Vatican Council. The monastery remains a place of spirituality and preserves a rich heritage, which bears witness to the history and evolution of the community. Keywords History, Monastery, Canonesses, Holy Sepulchre, Saragossa.